Volume 5: Manufacturing Materials and Metallurgy; Marine; Microturbines and Small Turbomachinery; Supercritical CO2 Power Cycle 2012
DOI: 10.1115/gt2012-68415
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of an Operating Supercritical CO2 Brayton Cycle

Abstract: Supercritical CO2 (S-CO2) power cycles offer the potential for better overall plant economics due to their high power conversion efficiency over a moderate range of heat source temperatures, compact size, and potential use of standard materials in construction [1,2,3,4]. Sandia National Labs (Albuquerque, NM, US) and the US Department of Energy (DOE-NE) are in the process of constructing and operating a megawatt-scale supercritical CO2 split-flow recompression Brayton cycle with contractor Barber-Nichols Inc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The two fluid temperatures approach each other with driving force for heat transfer. Conboy et al [54] report that this can occur under two general conditions: i) when the hot-stream temperature reaches the inlet temperature of the cold-stream which can happen if the heat exchanger is over designed or at off-design conditions in a counter current heat exchanger if the heat capacities of the two fluids greatly differ as in the case of S-CO 2 case and ii) when one of the fluid streams approaches its critical point (or a phase change), causing large changes in heat capacity, for which, the heat transfer at the location of the pinch point can still be very high, because the local heat transfer coefficient can increase close approach to the critical point (or phase change). In the case of a regenerator heat capacity of the high pressure CO 2 stream is larger than in the low pressure leg by a factor of 2.…”
Section: Heat Transfer Issuesmentioning
confidence: 99%
“…The two fluid temperatures approach each other with driving force for heat transfer. Conboy et al [54] report that this can occur under two general conditions: i) when the hot-stream temperature reaches the inlet temperature of the cold-stream which can happen if the heat exchanger is over designed or at off-design conditions in a counter current heat exchanger if the heat capacities of the two fluids greatly differ as in the case of S-CO 2 case and ii) when one of the fluid streams approaches its critical point (or a phase change), causing large changes in heat capacity, for which, the heat transfer at the location of the pinch point can still be very high, because the local heat transfer coefficient can increase close approach to the critical point (or phase change). In the case of a regenerator heat capacity of the high pressure CO 2 stream is larger than in the low pressure leg by a factor of 2.…”
Section: Heat Transfer Issuesmentioning
confidence: 99%
“…Through the overview of the current transient analysis code development for nuclear application related Brayton cycle, we can find most of the codes are developed based on existing transient analysis codes with incorporating CO 2 property, turbomachinery models, and PCHE models. The validation work is based on experimental data produced by s-CO laboratory(SNL) [25], and the s-CO 2 integral experiment loop (SCIEL) constructed by Korea Atomic Energy Research Institute (KAERI) [26]. Component performance and cycle transient characteristics of these experiment facility are vital for validating the newly developed code.…”
Section: Introductionmentioning
confidence: 99%
“…The USA is currently taking the lead in developing supercritical CO 2 power generation systems. Sandia National Lab (SNL) has been implementing and improving a supercritical CO 2 power generation test loop since 2005 [4][5][6][7]. In collaboration with Barber-Nichols, SNL has developed technologies for the key components of supercritical CO 2 power generation systems and conducted compressor tests [4].…”
Section: Introductionmentioning
confidence: 99%
“…An immersion type of electric heater was used to make a high-temperature supercritical CO 2 , and two printed circuit heat exchangers (PCHEs) were manufactured as a recuperator. In recent publication [6,7], experimental results obtained in 2012 showed that net power of 15 kWe was generated at 10,500 kPa/477°C/50,000 rpm operating conditions. Bechtel Marine Propulsion Corporation (BMPC) including Knolls Atomic Power Laboratory and Bettis Atomic Power Laboratory also designed and built a 100-kWe supercritical CO 2 Brayton cycle integrated systems test experimental apparatus for evaluating the applicability of a supercritical CO 2 power generation system in a nuclear propulsion shipboard [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%